2005
DOI: 10.1111/j.0908-8857.2005.03289.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of large‐scale climatic fluctuations on survival and production of young in a Neotropical migrant songbird, the yellow warblerDendroica petechia

Abstract: Migrant songbirds are vulnerable to changes in climatic conditions on both the breeding and wintering grounds. For North American Neotropical migrants, the El Niño/Southern Oscillation (ENSO), via its effects on global precipitation and temperature, modulates the productivity of their temperate and tropical terrestrial ecosystems used during the course of their annual cycle. We evaluated how a densely nesting population of yellow warblers Dendroica petechia in a riparian forest in southern Manitoba, Canada, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 55 publications
(79 reference statements)
2
41
3
Order By: Relevance
“…1). Apparent annual survival of both male and female Mangrove Warblers breeding in Mexico is higher than that of male and female migratory Yellow Warblers breeding in Montana (Cilimburg et al 2002) and Manitoba (Mazerolle et al 2005). Similarly, using the avian-demographic-query interface available online from the Institute of Bird Populations (see Acknowledgments), survival rates from constant-effort mist netting for the Yellow Warbler average 51% across its entire North American range.…”
Section: Resultsmentioning
confidence: 99%
“…1). Apparent annual survival of both male and female Mangrove Warblers breeding in Mexico is higher than that of male and female migratory Yellow Warblers breeding in Montana (Cilimburg et al 2002) and Manitoba (Mazerolle et al 2005). Similarly, using the avian-demographic-query interface available online from the Institute of Bird Populations (see Acknowledgments), survival rates from constant-effort mist netting for the Yellow Warbler average 51% across its entire North American range.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancements to the generalized model might be implemented within an adaptive management framework, through a flexible Bayesian approach (Frigessi et al, 2005) or through other methods of incorporating data from multiple sources and of varying reliability (Linacre et al, 2004). The generalized population matrix also provides a foundation for localized models directed toward managing single species in specific situations, which might incorporate collateral data, local environmental variation, stochastic environmental events (Lande, 1993), and population-specific demographic parameters (Dugger et al, 2004;LaHaye et al, 2004;Mazerolle et al, 2005). Similarly, the demographic parameters and error estimates presented above might be used singularly or in sets to enhance single species vital-rate based simulation models or population viability analyses.…”
Section: Resultsmentioning
confidence: 99%
“…we fitted each netted bird with a numbered aluminum Canadian wildlife Service leg band, identified each bird to species, and aged and sexed it according to Pyle (1997). we defined each site's productivity as the ratio of Hy to AHy birds netted, where the assumption is that capture probabilities for Hy and AHy birds are the same within a site (DeSante and geupel 1987, Koford et al 1994, Peach et al 1996, Bart et al 1999, Nott et al 2002, Mazerolle et al 2005, gaston et al 2006). …”
Section: Measures Of Productivitymentioning
confidence: 99%
“…Influences of NAO differ on each side of the Atlantic; positive NAO indices are associated with increased temperature and precipitation in northern Europe, but the opposite is true in eastern Canada (Ottersen et al 2001(Ottersen et al ). weatherhead (2005 reported high NAO values associated with higher productivity of successful nests, and Mazerolle et al (2005) reported both adult survival and productivity of yellow warblers (Dendroica petechia) positively correlated with SOI. for islands such as Newfoundland, climate is significantly influenced by the surrounding ocean.…”
Section: Annual Weather Variationmentioning
confidence: 99%